Biodegradable MoOx nanoparticles with efficient near-infrared photothermal and photodynamic synergetic cancer therapy at the second biological window. Issue 3 (5th January 2018) - Yin, Wenyan; Bao, Tao; Zhang, Xiao; Gao, Qin; Yu, Jie; Dong, Xinghua; Yan, Liang; Gu, Zhanjun; Zhao, Yuliang
Abstract : Biodegradable MoO x nanoparticles not only can convert light into heat but also generate ROS which realized synergic mild PTT and PDT under NIR-II laser (1064 nm) irradiation. Abstract : Near-infrared (NIR) laser induced phototherapy has been considered as a noninvasive option for cancer therapy. Herein, we report plasmonic PEGylated molybdenum oxide nanoparticles (PEG-MoO x NPs) that were synthesized by using a facile hydrothermal method. The PEG-MoO x NPs exhibit broad absorption at the NIR biological window and remarkable photothermal conversion ability in the first (808 nm) and the second (1064 nm) windows. Moreover, the biocompatible PEG-MoO x NPs exhibit effective cellular uptake and could be eliminated gradually from the liver and spleen in mice. Studies on the therapeutic effects of these NPs under 808 and 1064 nm exposures with mild hyperthermia are conducted. According to the result, exposure to 1064 nm irradiation can not only effectively convert light into heat but also sensitize the formation of reactive oxygen species (ROS), which exert dramatic cancer cell death and suppression in vivo due to the synergic effect of photothermal therapy (PTT) and photodynamic therapy (PDT). In marked contrast, 808 nm irradiation can only execute limited PTT to cancer cells, showing a relatively low inhibition rate in vitro and in vivo . This biodegradable MoO x nanoplatform with synergetic PTT and PDT functionalities upon 1064 nm irradiation provided emerging opportunities for the phototherapy of cancer in nanomedicine.